TO THE QUESTION OF REGIONAL ISSUES AND SITUATIONS IN THE ECONOMIC ASPECT - Sofya Aykazovna Tsaturyan (Современная наука и инновации)
The article deals with the theoretical aspects of state regulation of regional development, analyzes the socioeconomic development and the problems of regions of the Russian Federation, shows the strategic objectives of regional political at the present stage